Pathways of development of oxide dispersion-strengthened alloys - Luptáková, Natália; Bártková, Denisa (Frontiers in Materials, 2025)
Oxide dispersion-strengthened (ODS) alloys are considered promising structural materials for advanced applications, particularly in nuclear reactors, due to their excellent high-temperature strength and creep, oxidation, and irradiation resistance. They achieve these properties through a homogeneous dispersion of stable oxide nanoparticles in a metallic matrix, impeding dislocation motion. The main differences between conventional ODS alloys and newly developed ODS nanocomposites are also focused in this review. A recent state-of-the-art summary devoted to their processing, properties, and application potential is presented in the paper. Although traditional manufacturing methods such as mechanical alloying (MA) and subsequent consolidation are already approved, additive manufacturing (AM) is an emerging technology offering the potential to produce parts of complex geometries. Thus, the review also deals with the problems of 3D printing of ODS alloys. The prospects for ODS nanocomposites are critically assessed.